2009
DOI: 10.2527/jas.2008-1017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic markers for productive life in commercial sows1

Abstract: Escalating replacement rates and production costs warrant attention on sow productive life (SPL). Increasing average SPL by one-tenth of 1 parity would result in an annual revenue increase of over $15 million in the United States. Research in model organisms has revealed conserved genes and gene pathways that lead to longer lifespan. The most prominent gene pathways are those involved in growth, most notably genes in the IGF pathway that serve to mimic the response of caloric restriction. The objective of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
(16 reference statements)
1
24
0
1
Order By: Relevance
“…Initial analysis of American Yorkshire and Landrace populations indicated that several markers were significantly associated with either sow survival or reproductive traits (Mote et al, 2009). Markers selected from these preliminary data were evaluated in 2 Finnish pig populations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial analysis of American Yorkshire and Landrace populations indicated that several markers were significantly associated with either sow survival or reproductive traits (Mote et al, 2009). Markers selected from these preliminary data were evaluated in 2 Finnish pig populations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent association analysis (Mote et al, 2009), the most promising markers for sow survival were within genes C-C chemokine receptor 7 (CCR7) and CP-T1A. The CPT1A gene codes for an enzyme involved in the transport of certain long-chain fatty acids into mitochondria, a process essential to the production of ATP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations